2019
DOI: 10.1016/j.bbrep.2019.100631
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a monoclonal antibody PMab-233 for immunohistochemical analysis against Tasmanian devil podoplanin

Abstract: Monoclonal antibodies (mAbs) against not only human, mouse, and rat but also rabbit, dog, cat, bovine, pig, and horse podoplanins (PDPNs) have been established in our previous studies. PDPN is used as a lymphatic endothelial cell marker in pathological diagnoses. However, mAbs against Tasmanian devil PDPN (tasPDPN), which are useful for immunohistochemical analysis, remain to be developed. Herein, mice were immunized with tasPDPN-overexpressing Chinese hamster ovary (CHO)-K1 (CHO/tasPDPN) cells, and hybridomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…One formalin-fixed paraffin-embedded (FFPE) tissue sample from an oropharyngeal squamous cell carcinoma patient who underwent surgery at Sendai Medical Center was used for this study ( 13 ). Written informed consent was obtained from the patient for sample procurement and subsequent data analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One formalin-fixed paraffin-embedded (FFPE) tissue sample from an oropharyngeal squamous cell carcinoma patient who underwent surgery at Sendai Medical Center was used for this study ( 13 ). Written informed consent was obtained from the patient for sample procurement and subsequent data analyses.…”
Section: Methodsmentioning
confidence: 99%
“…CBIS has previously been used for developing several mAbs against various proteins, including the five transmembrane protein CD133 (7). Using the CBIS method, we have successfully produced sensitive and specific mAbs useful for not only flow cytometry, but also western blot and immunohistochemical analyses (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the critical epitope of PMab-237 could include Leu82 and Thr84 of wPDPN using the deletion mutants and point mutants of wPDPN in CHO-K1 cells by flow cytometry. In our previous studies, we developed many mAbs against PDPNs of human, (24) mouse, (25) rat, (26) rabbit, (27) dog, (28) cat, (29) bovine, (30) horse, (31) Tasmanian devil, (32) alpaca, (33) bear, (34) tiger, (35) goat, (36) pig, (37,38) and whale. (20) We successfully determined the binding epitope of those mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…The P3U1, CHO-K1, CHO/bPDPN, CHO/hPDPN [ 22 ], CHO/mouse PDPN (mPDPN) [ 22 ], CHO/rat PDPN (rPDPN) [ 10 ], CHO/rabbit PDPN (rabPDPN) [ 11 ], CHO/dog PDPN (dPDPN) [ 13 ], CHO/bovine PDPN (bovPDPN) [ 12 ], CHO/cat PDPN (cPDPN) [ 14 ], CHO/pig PDPN (pPDPN) [ 15 ], CHO/horse PDPN (horPDPN) [ 16 ], CHO/tiger PDPN (tigPDPN) [ 18 ], CHO/alpaca PDPN (aPDPN) [ 19 ], CHO/Tasmanian devil PDPN (tasPDPN) [ 21 ], CHO/goat PDPN (gPDPN) [ 17 ], CHO/sheep PDPN (sPDPN) [ 23 ], and CHO/whale PDPN (wPDPN) [ 20 ] were cultured in a Roswell Park Memorial Institute (RPMI) 1640 medium (Nacalai Tesque, Inc.), supplemented with 10% of heat-inactivated fetal bovine serum (FBS; Thermo Fisher Scientific Inc.), 100 units/mL of penicillin, 100 μg/mL of streptomycin, and 25 μg/mL of amphotericin B (Nacalai Tesque, Inc.). The cells were grown in an incubator at 37 °C with humidity and 5% CO 2 and 95% air atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed monoclonal antibodies (mAbs) against human [ 6 ], mouse [ 9 ], rat [ 10 ], rabbit [ 11 ], bovine [ 12 ], dog [ 13 ], cat [ 14 ], pig [ 15 ], horse [ 16 ], goat [ 17 ], tiger [ 18 ], alpaca [ 19 ], whale [ 20 ], and Tasmanian devil [ 21 ] PDPNs. In this study, we immunized mice with CHO/bear PDPN (bPDPN) cells and established mAbs against bPDPN.…”
Section: Introductionmentioning
confidence: 99%